Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Integumen (Snake Bite) di Ruang Anggrek RSUD Banjar - Muhamad Ramdan Nujulul Furqon; Ade Fitriani; Gumilar Rahmat (KOLABORASI JURNAL PENGABDIAN MASYARAKAT, 2022)
Introduction: Snakebite is a disease of the integumentary system that causes pain for the sufferer and can even result in disability and death. Objective: This assistance aims to provide a nursing plan to Mrs. O with a medical diagnosis of snake bite in the Anggrek room at the Banjar Hospital in 2022. Method: Assistance activities are carried out by providing nursing care through 5 stages of the nursing process, namely Assessment, Diagnosis, Nursing Intervention, Nursing Implementation, and Evaluation. Result: The results showed that the patient's main complaint was pain, the diagnosis that appeared in the patient was acute pain, after being given nursing actions since January 5, the results showed that the patient said he had relaxed a little. Conclusion: After the process of providing nursing care was carried out on January 5, 2022, the nursing problems found in Ny. O is not resolved and continue the intervention.